FRI0196 Comparison between ultrasonographic and clinical disease activity of rheumatoid arthritis in patients two years treated with anti tnf biological therapy. (23rd January 2014) - Prodanovic, S. Z.; Radunovic, G.; Zivojinovic, S.; Seric, S.; Damjanov, N.; Zlatanovic, M.
Abstract : Objectives: To compare disease activity in patients with rheumatoid arthritis (RA) after two years treatment with anti TNF therapy estimated by ultrasound and clinical examination (US) of 28 joints. Methods: A total 30 RA pts. after anti TNF (Etanercept) treatment lasting for two years, were enrolled in study. Seventy three percent (22/30) of pts. were female, the mean age of patients was 52.7±9.4 yr. The mean duration of the disease was 132±94.0 months. Ultrasound examination of 28 joints included in DAS 28 was performed by Esaote My Lab 70 machine equipped 8-18 MHz linear probe. The total number of 840 joints were examined. The presence of joint effusion and Power Doppler (PD) signal was assessed qualitatively, (present or not). The simultaneous presence of joint effusion and PD signal at the same joint, were considered as ultrasonographic sign of disease activity. RA disease activity was assessed by DAS-28. All pts. were completed HAQ. Structural joint damage was evaluated by Sharp/van der Heijde method. The pts. with RA remission (the value of DAS-28<2.6) and low (the value of DAS-28 3.2≥ 2.6) disease activity were further analyzed. The data were analyzed in SPSS system. Results: The mean value of DAS 28 was 3.4±1.4, HAQ 0.5±0.5 and Sharp/van der Heijde score 101.1±63.4.5. The pts. had 5.5 joints with effusion and 1.2 joints with positive PD signal in average by US in opposite to 1.4 swollen and 2.7 painful joints in average by clinical examination. Only one patient had no evidence of joint effusion while thirteen (43%) had no PD signal presence by ultrasound examination in contrast to fifteen (50%) pts. without swollen and twelve (40%) pts. without painful joints by clinical examination. Nineteen (57.5%) pts. had ultrasonographic sign of disease activity. Six pts. were found with DAS 28 remission. The frequency of ultrasonographic evidence of disease activity was present at 33.3% of pts. in contrast to 62.5% of pts.with value of DAS>2.6. The difference was not statistically significant (p=0.360). Thirteen pts. were found with low disease activity according to DAS 28. The frequency of ultrasonographic evidence of disease activity was present at 62% of pts. in opposite to 53 % of pts.with very active RA. The difference was not statistically significant (p=0.721). Conclusions: Despite signs of RA remission or low disease activity according to DAS 28, patients had some evidence of joint inflammation confirmed by ultrasound after two years of treatment with anti TNF therapy. Disclosure of Interest: None Declared